Applicability, optimization and performance comparison of self-preheated solar collector/regenerator. (1st March 2020) - Peng, Donggen; Cao, Zhuo; Fu, Yuting; Li, Shuangling; Yang, Zexuan
Highlights: A novel self-preheated solar collector/regenerator is proposed. There are optimal proportion of collector length for the self-preheated C/R. There are optimal flow-rates of air and solution and glazing height for the self-preheated C/R. Self-preheated solar C/R has greater superiority under humid and low solar radiation environment. Abstract: In this paper, a self-preheated solar collector/regenerator (C/R) is proposed to conquer the anti-regeneration phenomenon of traditional solar C/R in order to increase its regeneration efficiency. Through numerical simulation, the applicability of the self-preheated C/R in Northern and Southern cities of China and parameter optimization as well as the performance comparisons with the traditional C/R are conducted. The research results show the self-preheated C/R has good applicability for the 24 cities chosen in China, but the length of collector section is selected in the optimum ranges. The optimal proportion of collector length in the southern China is in the range of 0.4–0.55 while it focusing on 0.35–0.5 in the northern China. In the optimization of parameters, the best flow-rates of air and solution for the unit area of C/R fall into the ranges of 50–100 kg/(m 2 ·h) and 3–6 kg/(m 2 ·h) respectively, and the height of C/R glazing should be maintained at 0.04–0.06 m for higher regeneration efficiency of the device. By comparing to the performance of traditional C/R, the self-preheated solar C/R has greater superiority at higher ambient relative humidity, lower solution temperature and higher solution concentration as well as lower solar radiation intensity. The increased extent can reach as much as 22% at ξ in = 0.4 kg/kg. The total length of self-preheated C/R has an optimal value on the performance of device. All these results can provide guidance for performance analysis and application of the novel solar collector/regenerator.